Question 2.
Given the system of equations:
• -x + y = 1
,
• x + y = 11
Let's solve the system by elimination method using addition and subtraction.
To solve the system, add both equations to eliminate the x variable.
-x + y = 1
+ x + y = 11
__________
2y = 12
Divide both sides of the equation by 2:
![\begin{gathered} (2y)/(2)=(12)/(2) \\ \\ y=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9l425jonvdf236vfchebk9rt0p3yit113l.png)
Now, substitute 6 for y in either of the equations:
Let's take the second equation
![\begin{gathered} x+y=11 \\ \\ x+6=11 \\ \\ \text{Subtract 6 from both sides:} \\ x+6-6=11-6 \\ \\ x=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xnv5166l0uz0srep179ywssbohsrbhdwmm.png)
Therefore, we have the solution:
x = 5, y = 6